World political theatre and performance theories, histories, practices - Aragay, Mireia; Botham, Paola; Prado-Perez, Jose Ramon (Leiden ; Boston Brill Rodopi, 2020)
World Political Theatre and Performance brings together scholars and practitioners from multiple locations to analyse counter-hegemonic theatre and performance. International case studies are framed by a common reflection on the meaning of radical practice in the face of global neoliberalism.
Keywords: Theater -- History; Theater -- Production and direction; Theater -- Political aspects